2016
DOI: 10.1186/s12866-016-0845-x
|View full text |Cite
|
Sign up to set email alerts
|

The succession pattern of soil microbial communities and its relationship with tobacco bacterial wilt

Abstract: BackgroundThe interaction mechanism between crop and soil microbial communities is a key issue in both agriculture and soil ecology. However, how soil microbial communities respond to crop planting and ultimately affect crop health still remain unclear. In this research, we explored how soil microbial communities shifted during tobacco cultivation under different rotation systems (control, maize rotation, lily rotation and turnip rotation).ResultsOur analyses showed that soil microbial communities had a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 39 publications
(42 reference statements)
4
35
0
Order By: Relevance
“…DNA extraction, amplification of 16S rRNA amplicons and sequencing were performed as described in our previous studies ( Niu et al, 2016 ; Niu et al, 2017 ). Briefly, DNA were extracted using a MO BIO PowerSoil DNA Isolation Kit (MO BIO, San Diego) following the manufactures’ manual.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA extraction, amplification of 16S rRNA amplicons and sequencing were performed as described in our previous studies ( Niu et al, 2016 ; Niu et al, 2017 ). Briefly, DNA were extracted using a MO BIO PowerSoil DNA Isolation Kit (MO BIO, San Diego) following the manufactures’ manual.…”
Section: Methodsmentioning
confidence: 99%
“…Using a high-through put sequencing approach, Wang et al (2017) found the microbial community was different between healthy and bacterial wilt-infected fields. Niu et al (2016) also found that cropping regimes affected plant disease outbreaks by changing the soil microbial communities. Addition of organic fertilizers could inhibits plant diseases through alteration of soil microbial composition, diversity, and activity ( Hunter et al, 2006 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Soil microorganisms play vital roles in the maintenance of soil function [15] and significantly influence agricultural soil productivity, plant growth, and crop quality [16][17][18]. Numerous studies have suggested that microbial diversity can serve as an indicator of disease susceptibility in medicinal plants, and microbial communities have important roles in the maintenance of plant health and soil fertility [19][20][21]. For example, a lack of diversity among beneficial microbial communities like that of Alteromonadales, Burkholderiales, and Flavobacteriales, may be an important factor contributing to the decline in peanut yield under continuous cropping [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, plants can alter soil microbes through the secretion of root exudates, and on the other hand, soil microbes have the ability to influence the productivity, diversity, and health of plants (Chaparro et al 2012 ). Some studies found that the changes in soil microbial community structure were related to the occurrence of soil-borne wilt (Bernard et al 2012 ; Niu et al 2016 ; Wu et al 2016 ).With manipulation of the rhizosphere microbial community, suppression of soil-borne diseases can be enhanced (Mazzola 2007 ; Qiu et al 2012 ; Shen et al 2015 ; Yao and Wu 2010 ). Furthermore, soil pH was the strongest factor that determines microbial community composition, and bacterial relative abundance and diversity is positively affected by soil pH and soil acidification amendments can regulate soil pH (Hartman et al 2008 ; Lauber et al 2009 ; Zhalnina et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%